THE ESSENCE OF THE CONTENT OF “INCLUSIVE” AND “INTEGRATED” EDUCATION - Rakhımova Khurshıdakhan Sadıkovna; Sattorova Dildora Mirzaakbarovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information on Inclusive Education and integration. The article also covers the problems in the involvement of a defective child in inclusive education and their solutions.